SAFAX – An Extensible Authorization Service for Cloud Environments - Kaluvuri, Samuel Paul; Egner, Alexandru Ionut; den Hartog, Jerry; Zannone, Nicola (Frontiers in ICT, 2015)
Cloud storage services have become increasingly popular in recent years. Users are often registered to multiple cloud storage services that suit different needs. However, the ad-hoc manner in which data sharing between users is implemented leads to issues for these users. For instance, users are required to define different access control policies for each cloud service they use and are responsible for synchronizing their policies across different cloud providers. Users do not have access to a uniform and expressive method to deal with authorization. Current authorization solutions cannot be applied as-is, since they cannot cope with challenges specific to cloud environments. In this paper, we analyze the challenges of data sharing in multi-cloud environments and propose SAFAX, an XACML based authorization service designed to address these challenges. SAFAX's architecture allows users to deploy their access control policies in a standard format, in a single location, and augment policy evaluation with information from user selectable external trust services. We describe the architecture of SAFAX, a prototype implementation based on this architecture, illustrate the extensibility through external trust services and discuss the benefits of using SAFAX from both the user's and cloud provider's perspectives.